Cycloaddition of cyclobutenone and azomethine imine enabled by chiral isothiourea organic catalysts - Li, Bao-Sheng (2015)
The addition of an organic catalyst to the ketone moiety of a γ-mono-chloride substituted cyclobutenone destroys its stable, conjugated and nearly planar structure. The C–C bond in the resulting less stable anionic oxy-substituted non-planar intermediate is then activated. The breaking of one C–C single bond leads to a catalyst-bound intermediate that undergoes α-carbon selective reactions with azomethine imines to afford nitrogen-containing heterocyclic compounds with excellent diastereo- and enantio-selectivities. Our organocatalytic approach provides a new reaction pattern for C–C bond activation of cyclobutenones that is unavailable with transition metal catalysis. In addition, the present study with isothioureas as the organocatalysts expands the potential in using organocatalysts for C–C bond breaking and selective reactions.